Determinan Agresivitas Pajak Pada Perusahaan Pertambangan Yang Terdaftar Pada Bursa Efek Indonesia - Sari, Erika Novita; Chairina, Septi Wulandari (Universitas Muhammadiyah Jakarta, 2024)
Objectives: This study aims to evaluate the impact of profitability, transfer pricing, and thin capitalization on tax aggressiveness, with company size acting as a moderating variable. Design/method/approach: Employing a quantitative approach, this research utilizes secondary data sources from published financial reports. The population comprises mining companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021, with purposive sampling employed for sample selection. The chosen sample includes 13 companies, totaling 65 data observations. Panel data regression analysis is conducted using the E-views 10 application program for data analysis.Results/findings: The study reveals that profitability and transfer pricing do not exert a significant effect on tax aggressiveness. However, thin capitalization and company size demonstrate a significant impact on tax aggressiveness. Regarding moderation, company size moderates the influence of profitability and thin capitalization on tax aggressiveness, while it does not moderate the impact of transfer pricing on tax aggressiveness. Theoretical contribution This study serves as a valuable reference for understanding the determinants of tax aggressiveness. Practical contribution: The study aims to offer important insights for the government to strengthen tax regulations, minimizing